Domestic product of states of India; 1960 - 61 to 2000 - 01 - EPW Research (Mumbai, 2003)
The EPW Research Foundation (EPWRF) is pleased to publish, as part of its activities of building data base on the Indian economy, this volume On Domestic product of States of India : 1960-61 to 200-01, a first of its kind in India. Until the third edition of its publication national Accounts Statistics of India. Research scholars, both in India and abroad, have been seeking such a single publication presenting all data on state domestic product available on a comparable basis for different periods in the post-independence period.
Keywords: Domestic product - India